Local anesthesia versus saddle block for open hemorrhoidectomy: cost-analysis from a randomized, double blind controlled trial - Sikakulya FK; Ssebuufu R; Okedi XF; Baluku M; Lule H; Kiyaka SM; Muhumuza J; Molen SF; Bassara GN; Waziri MA; Kithinji SM; Leocadie MM; et al. (United Kingdom, 2025)
Background: Despite the benefits attributed to the use of local anesthesia (LA) for open hemorrhoidectomy (OH) in developed countries, this technique is still not considered as the first line technique in low-income countries such as Uganda; therefore, we aimed at comparing the cost of OH under LA versus Saddle block among patients with 3rd or 4th degree hemorrhoids.
Methods: This trial was conducted from December 2021 to May 2022 among patients with primary uncomplicated 3rd or 4th degree hemorrhoids. The operating time, and direct costs in (US$) including medical and non-medical were recorded. We analysed the cost in the two groups (local anesthesia versus saddle block) using SPSS version 23.0.
Results: Findings of fifty-eight patients were analysed including 29 participants per group. There was a significant difference in operating time and cost among the two groups (p < 0.05). The mean operating time was 15.52 ± 5.34(SD) minutes versus 33.72 ± 11.54 min for OH under LA and SB respectively. The mean cost of OH under LA was 57.42 ± 8.90 US$ compared to 63.38 ± 12.77US$ in SB group.
Conclusion: The use of local anesthesia for OH was found to have less operating time with high-cost effectiveness. Being affordable, local anesthesia can help to increase the turnover of patients who would otherwise wait for the availability of anesthesia provider. Policy makers should emphasize its applicability in low-income settings to help in the achievement of 2030 global surgery goals.